Which witch? - Ibbotson, Eva.; Large, Annabel (New York : Dutton Children's Books, 1999)
Deciding that he must sire a child to carry on his tradition of Loathing Light and Blighting the Beautiful, the Great Wizard Arriman announces a competition among the witches of Todcaster, one of whom will marry him.
Keywords: Witches; Wizards; Magic; Contests